Metalloproteinases 2 and-9 activity during promotion and progression stages of rat liver carcinogenesis - Furtado, Kelly Silva [UNESP]; Pires, Paulo Wagner; Justulin, Luis Antonio [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Felisbino, Sergio Luis [UNESP]; Barbisan, Luis Fernando [UNESP] (Springer, 2009)
Activity of metalloproteinases 2 and 9 (MMP-2 and 9) during promotion and progression of rat liver carcinogenesis was investigated in a modified resistant hepatocyte model. Development of preneoplastic liver lesions positive for glutathione S-transferase 7-7-(GST-P 7-7-positive PNL) and tumors besides hepatocytes positive for proliferating cell nuclear antigen (PCNA) were quantified and compared to MMP-2 and-9 activity using gelatin zymography. Marked increases in GST-P 7-7-positive PNL development, PCNA labeling indices, MMP-2 (pro, intermediate and active forms) and pro-MMP-9 activity were observed after proliferative stimulus induced by 2-acetylaminofluorene (2-AAF) exposure cycles. After 2-AAF withdrawal, increase in MMP-2 activity was detected only in neoplastic mixed lesions, whereas active MMP-9 was increased in both PLN and neoplastic tissues. Our findings suggest that MMP-2 may be associated with proliferative events induced by 2-AAF rather than with selective growth of PNL and that MMP-9 could be associated with progression of PNL and neoplastic mixed lesions.
Keywords: Rat liver carcinogenesis; Resistant hepatocyte model; Metalloproteinases; Preneoplastic and neoplastic lesions